Estimasi Simpanan Karbon dan Status Kesehatan Padang Lamun di Pulau Kelapa Kabupaten Bima - Isnaini Marliana; Hilman Ahyadi; Dining Aidil Candri; Immy Suci Rohyani; Sukmaraharja Aulia Rachman Tarigan; Pardede Shinta Trilestari; Sebastian Aviandhika; Sri Puji Astuti (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The seagrass community are angiosperm plant communities that mostly grow in shallow marine waters. The community has an ecological role and function, both as a habitat for various types of biota and as a carbon sink. The purpose of this study was to determine the type and condition of the seagrass ecosystem in Kelapa Island based on the percentage of cover; and to determine the estimated carbon stocks of seagrasses contained. Seagrass community data collection was carried out in September-October 2020 in the waters of Kelapa Island, Bima Regency, West Nusa Tenggara Province. A quadratic transect was used for data collection of seagrass cover, and analysis of seagrass community cover using the PhotoQuad application, followed by determining the condition of the seagrass community ecosystem, and analysis of estimated carbon storage using the Loss On Ignition (LOI) method. The results showed that there were 4 types of seagrass found, consisting of: Thalassia hemprichii, Halophila ovalis, Cymodocea rotundata, and Halodule pinifolia. The percentage of seagrass cover is 52.31%, because it is less than 60%, the health status of seagrass beds is unhealthy based on the Decree of the Minister of the Environment Number 200 of 2004. Total carbon storage is 16.1 gr.Cm-2. Thalassia hemprichii as the highest carbon storage species was 8.27 gr.Cm-2.